ICTs AND EMPLOYMENT: NEW OPPORTUNITIES ON THE LABOUR MARKET - SURUGIU, Marius; SURUGIU, Camelia; MAZILESCU, Raluca (Annals of Spiru Haret University. Economic Series, 2018)
Objectives: In this paper, the potential for increasing employment opportunities and skills availability is investigated. Prior work: E-work activities differ by countries, with impact in various fields. Approach: The statistical data are used to underline the trends. Results: E-work is an emerging process and supports the development of a new business model. Implications and value: From the businesses perspective, e-work phenomenon may represent a new opportunity, and competitiveness could be improved. Also, e-work may present advantages and disadvantages with influences on the results of workers and businesses. In this paper such trends are analysed, in a comparative approach.